One Day, One Color Qur'an Memory Strategy in The Boarding School Management - Hudallah Zufa; Meti Fatimah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
AbstractThis study aims to analyse the One Day One Colour strategy in the Qur'an memorisation program and its impact on the motivation and participation of students at MTs Negeri 3 Demak, a boarding school institution. The One Day One Colour strategy integrates Al-Qur'an memorisation into the daily routine of students by utilising colour as a visual code and daily theme to facilitate the recognition of memorisation targets, increase engagement, and make the muraja'ah process more varied and enjoyable. The study used a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation, and analysed using the Miles and Huberman model through interactive reduction, presentation, and conclusion drawing. The results of the study indicate that the One Day One Colour strategy at MTs Negeri 3 Demak is an innovative and comprehensive approach to learning Al-Qur'an memorisation in a boarding school environment, because it is able to integrate cognitive, affective, and managerial aspects in an integrated manner. The use of colour as a visual code for daily memorisation targets makes it easier for students to remember and monitor memorisation achievements, while increasing motivation, emotional involvement, and interest in learning. This strategy forms a culture of memorising the Qur'an as a daily routine that is integrated with all student activities, and is supported by continuous supervision and coordination between teachers, caregivers, and the head of the madrasah, so that it effectively improves the quality of memorisation, student participation, and internalisation of spiritual values and self-discipline.